Prognostic value of pan-immune-inflammation value in colorectal cancer patients: A systematic review and meta-analysis - Yang, Xiao-Chuan; Liu, Hui; Liu, Ding-Cheng; Tong, Chao; Liang, Xian-Wen; Chen, Ri-Hui (Frontiers in Oncology, 2022)
Background: Recently, the pan-immune-inflammation value (PIV) has been reported as a novel prognostic biomarker in multiple malignancies. The aim of this study is to investigate the prognostic value of the PIV in patients with colorectal cancer. Methods: We comprehensively searched electronic databases including PubMed, Embase and Web of Science up to August 2022. The endpoints were survival outcomes. Hazard ratios (HRs) with 95% confidence intervals (CIs) for survival data were collected for analysis. Results: Six studies including 1879 participants were included. The combined results indicated that patients in the high baseline PIV group had a worse overall survival (HR=2.09; 95%CI: 1.67-2.61; P<0.0001; I2=7%) and progression-free survival (HR=1.82; 95%CI: 1.49-2.22; P<0.0001; I2=15%). In addition, early PIV increase after treatment initiation was significantly associated with decreased overall survival (HR=1.79; 95%CI: 1.13-2.93; P=0.01; I2=26%), and a trend toward poor progression-free survival (HR=2.00; 95%CI: 0.90-4.41; P=0.09; I2=70%). Conclusion: Based on existing evidence, the PIV could act as a valuable prognostic index in patients with colorectal cancer. However, more high quality studies with large sample size are required to further validate this issue.